Deciphering the role of QPCTL in glioma progression and cancer immunotherapy - Liu, Yu’e; Lu, Shaojuan; Sun, Yihong; Wang, Fei; Yu, Shibo; Chen, Xi; Wu, Lei-lei; Yang, Hui; Shi, Yufeng; Zhao, Kaijun (Frontiers in Immunology, 2023)
Targeting the immune checkpoint CD47 or blocking the CD47-SIRPα axis can effectively eliminate glioma cancer cells but also brings side effects such as anemia. Glutaminyl-peptide cyclotransferase-like protein (QPCTL) catalyzes the pyroglutamylation of CD47 and is crucial for the binding between CD47 and SIRPα. Targeting QPCTL rather than CD47 avoid the side effect since it isn’t expressed in erythrocytes. Further study found that loss of intracellular QPCTL restricts chemokine function and modulates myeloid infiltration to potentiate tumor immunity[1]. Therefore, deciphering the function of QPCTL in glioma progression and cancer immunotherapy is necessary for glioma treatment. Through comprehensive analysis via different databases, we found that the expression of QPCTL was higher in glioma tumor tissue in contrast to normal tissue. Higher QPCTL expression was positively related with high-grade malignancy and advanced tumor stage. The DNA methylation of QPCTL is lower in gliomas than that in normal sample. The survival analysis indicates that glioma patients with higher QPCTL expression and lower DNA methylation level is shorter than those with lower QPCTL expression and higher DNA methylation level. The expression of QPCTL is highly associated with the immune infiltration especially the monocytes and macrophage infiltration. Moreover, QPCTL is essential for glioma cell proliferation and tumor growth and is positive correlation with glioma cell stemness. Targeting QPCTL will be a promising immunotherapy in glioma cancer treatment.